Evolução cromossômica em plantas de inselbergues com ênfase na família Apocynaceae Juss - Santos, Angeline Maria da Silva (2017)
The inselbergs are characterized by presenting more severe edaphoclimatic conditions in relation to the surrounding environment, exerting an important selective function for the evolution and vegetal speciation. The flora of the inselbergs can present morphological and chromosomal differentiation (levels of ploidy), making possible the evaluation of the mechanisms involved in the diversification of the species. A long-debated hypothesis suggests that polyploids exhibit greater tolerance to more extreme environmental conditions when compared to their diploid counterparts. The objective of this work was to analyze 28 species belonging to 10 different families of angiosperms, occurring in inselbergues in the Northeast region of Brazil, with an emphasis on the Apocynaceae family. The root tips were pretreated with 8HQ and Colchicine (only the Costaceae family species) and fixed in Carnoy. The slides were prepared by the method of crushing in acetic acid and aged at room temperature. Then, the best slides were stained with chromomycin (CMA) and 4 ', 6-Diamidino-2-Phenylindole (DAPI) and photographed. The species of Apocynaceae ranged from 2n = 18 to 2n = 34, with new data for six species. Three types of heterochromatic bands were identified in family Apocynaceae species: CMA+ /DAPI-, CMA- /DAPI+ and CMA0/DAPI+ bands, varying in the pattern of distribution, number and size of heterochromatic bands. CMA+/DAPI- bands were observed in all species analyzed, and probably is the type of heterochromatin associated with RONs.The species analyzed ranged from 2n = 18 para Chamaecostus subsessilis (Costaceae) to 2n = 76 in Dichorisandra hexandra (Commelinaceae). Polyploidy and dysploidy are the main mechanisms of karyotype evolution involved in the diversification in Apocynaceae, with the diploid species being most frequently found in inselbergues. Among the analyzed genera there is no clear relationship between the number of CMA+ bands and the level of ploidy. Of the 28 species occurring in inselbergues in northeastern Brazil, only seven are polyploid, occurring especially in the Apocynaceae, Commelinaceae, Euphorbiaceae and Melastomataceae families. In addition, the preferential occurrence of polyploid cytotypes on inselbergues was not observed for these species, refuting the hypothesis that poliploids present greater tolerance to more extreme edaphoclimatic conditions.